Peran Thariqat Qadiriyah An Naqsyabandiyah Dalam Membentuk Budaya Religius - Josef Subagio; Farida Ulvi Naimah; Muslihun Muslihun (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
This research aims to analyze the role of the Qadiriyah and Naqsyabandiyah congregations in forming religious culture in the Roudlotut Ta'allum recitation congregation in North Anjatan Village, Anjatan District, Indramayu Regency. The Qadiriyah an Naqsyabandiyah order is a contemporary order combining two large orders, namely Qadiriyah and Naqsyabandiyah. This research uses a qualitative approach with a case study type of research. Primary data was obtained through interviews with congregation leaders, deputy leaders, community leaders, and congregation members. Secondary data is obtained from documentation in notes, reports, books, and other relevant scientific work. Data collection was carried out through interviews, observation, and documentation. Data analysis was done through data reduction, presentation, and conclusion. The validity of the data is guaranteed through increasing persistence, triangulation, and extension of observations. This research is important for understanding how congregations as socio-religious organizations can shape religious culture at the local level. Congregations have a role in shaping people's attitudes, character, and perspectives on religion and life. By examining the role of the Qadiriyah an Naqsyabandiyah Order in the context of the religious culture of the Roudlotut Ta'allum congregation, this research provides a new perspective in understanding the dynamics of the order and its influence on the lives of Muslim communities at the grassroots level. It is hoped that the findings of this research can contribute to the development of Sufism, Tariqah, and other related studies